Survey on the surfaces generated by generalized analytic functions - Beknazaryan, Aleksandr; Grigoryan, Suren (Armenian Journal of Mathematics, 2015)
In this paper some fundamental results from the theory of generalized analytic functions are presented. Then, based on that theory, we develop the theory of the so-called Bohr-Riemann surfaces.